The Present Tense Usage in Speaking Skill: An Analysis of Students' Short Speech Texts - Hafni Hafsah (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2020)
The result of this paper is based on the data taken from Triskanedi (2007). The study result showed that 80% of students made mistakes in the use of simple present tense, which was the highest compared to the other two tenses, namely simple past and simple future tense. Due to these interesting findings, the writer intended to carry out further analysis by using the data of the research to find out the kinds of errors produced by the students focusing on simple present tense usage in the short speech texts. The analysis of the data uses a specific type of errors, i.e., omission, addition, missed formation and missed ordering/improper ordering in accordance to taxonomy strategy. The result shows the percentage of the omission of 'be and s/es' is 41.08%. While the addition of 'be and s/es' is 6,21%, and missed formation is 51,94%, and improper ordering is only 0,77%. The omission and addition seem related to the use of 'be' before an adjective or nominal sentence and's' in subject-verb agreement. In addition, the study also found few other errors in using of article 'the', verb inflexion 'ed', and of auxiliary in small numbers. These seems contributed to the students' errors production despite the fact that simple present tense considered as the easiest one to formulate compared to others, another thing that needs to underlie from this study is the understanding of English grammar seems necessary to avoid the same errors in the future